2018
DOI: 10.1111/jth.13914
|View full text |Cite
|
Sign up to set email alerts
|

Procarboxypeptidase U (proCPU, TAFI, proCPB2) in cerebrospinal fluid during ischemic stroke is associated with stroke progression, outcome and blood–brain barrier dysfunction

Abstract: Background Procarboxypeptidase U (proCPU, TAFI, proCPB2), the zymogen of CPU, which is a potent antifibrinolytic enzyme and a modulator of inflammation, has previously been investigated in plasma of stroke patients, but so far, no information on the proCPU levels in cerebrospinal fluid (CSF) during acute ischemic stroke (AIS) is available. Objectives This case-control observational study investigates proCPU in CSF of AIS patients compared with controls with an intact blood-brain barrier (BBB) and evaluates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A loss of cholinergic neurons in 40% of demented vascular patients was reported, accompanied by reduced ACh activity in the cortex, hippocampus, and striatum [152]. Post-mortem SVD studies revealed lower choline acetyltransferase (ChAT) activity when compared with the controls [153], and SVD patients have lower CSF concentrations of Ach [151,[154][155][156]. In fact, in the experimental condition, the selective muscarinic antagonism by atropine, for example, has dramatic consequences in the CA1 region, [157].…”
Section: Cholinergic Role In Small Vessel Diseasementioning
confidence: 99%
“…A loss of cholinergic neurons in 40% of demented vascular patients was reported, accompanied by reduced ACh activity in the cortex, hippocampus, and striatum [152]. Post-mortem SVD studies revealed lower choline acetyltransferase (ChAT) activity when compared with the controls [153], and SVD patients have lower CSF concentrations of Ach [151,[154][155][156]. In fact, in the experimental condition, the selective muscarinic antagonism by atropine, for example, has dramatic consequences in the CA1 region, [157].…”
Section: Cholinergic Role In Small Vessel Diseasementioning
confidence: 99%
“…In non-thrombolysed patients, significant plasma proCPU activation (reflecting fibrinolytic activity and/or activation of the coagulation cascade) in the first 72 h after ischemic stroke onset was observed [35]. In the same study cohort, increased proCPU levels were measured in the cerebrospinal fluid of stroke patients [36]. More pronounced plasma proCPU consumption and increased proCPU levels in cerebrospinal fluid have been associated with blood-barrier dysfunction, stroke progression and poor outcome [35,36].…”
Section: Arterial Thrombosismentioning
confidence: 98%
“…In the same study cohort, increased proCPU levels were measured in the cerebrospinal fluid of stroke patients [36]. More pronounced plasma proCPU consumption and increased proCPU levels in cerebrospinal fluid have been associated with blood-barrier dysfunction, stroke progression and poor outcome [35,36]. Alessi et al demonstrated that stroke patients at admission had higher CPU + CPUi levels compared to control subjects and that CPU + CPUi levels were associated with stroke severity in non-thrombolysed patients [37].…”
Section: Arterial Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as a negative feedback regulator, i.e., inhibits fibrinolysis. In stroke patients TAFI is elevated in the acute phase of ischemia [92] and is associated with a poor outcome [93]. Furthermore, studies on murine stroke models have shown that anti-TAFI monoclonal antibodies (MA-TCK26D6) reduce fibrinogen deposition, hence improving reperfusion [94].…”
Section: Nanobodies As New Thrombolytic Agentsmentioning
confidence: 99%